Avaliação da citotoxicidade dos extratos da corrosão de mini-implantes ortodônticos de TI- 6AL-4V após imersão em saliva artificial fluoretada por 30, 90 ou 180 dias - Lemes, Sandra Stival dos Santos (2008)
The alloys used in the orthodontic therapy are subject to the corrosion process in the oral environment. Orthodontic mini-implants Ti-6Al-4V are an excellent source for intraoral anchorage; however, their corrosion resistance in the presence of fluoride is currently unknown. The purpose of this in vitro study was to evaluate the cytotoxic effects of the corrosion extracts of mini-implants Ti-6Al-4V from three different manufacturers when exposed to 200 g/L of sodium fluoride containing artificial saliva for 30, 90 or 180 days. The cytotoxic effects of their corrosion products on L929 cell culture was evaluated by MTT (3- [4,5-dimethylthiazol-2-yl]2,5-diphenyltetrazolium bromide) assay, for cell metabolism and proliferation. The extracts were not cytotoxic and the cytotoxicity assay demonstrated a similar behavior for the samples immersed in artificial saliva in the three evaluated periods. The qualitative analysis, through SEM did not show characteristics of corrosion. The results indicated that the mini-implants tested presented a high corrosion resistance and biocompatibility.